2022
DOI: 10.3390/diagnostics12071677
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Intraparenchymal Hemorrhage Progression and Neurologic Outcome in Traumatic Brain Injury Patients Using Radiomics Score and Clinical Parameters

Abstract: (1) Background: Radiomics analysis of spontaneous intracerebral hemorrhages on computed tomography (CT) images has been proven effective in predicting hematoma expansion and poor neurologic outcome. In contrast, there is limited evidence on its predictive abilities for traumatic intraparenchymal hemorrhage (IPH). (2) Methods: A retrospective analysis of 107 traumatic IPH patients was conducted. Among them, 45 patients (42.1%) showed hemorrhagic progression of contusion (HPC) and 51 patients (47.7%) had poor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Furthermore, there are studies describing models to predict the functional outcome or The Glasgow Outcome Scale-Extended, 5,[25][26][27][28][29] and more recent studies using images as inputs. 8,30,31 Furthermore, there are studies in the literature similar to ours that describe models for predicting in-hospital mortality, 29,[32][33][34][35] early mortality, [36][37][38] discharge position, 39,40 need for hospital admission, 6 emergency neurosurgery, 41 and length of hospital stay. 4 In addition to contributing to the body of knowledge by describing the efficacy of incorporating ML into patient care to predict multiple outcomes simultaneously in TBI patients, this study is unique since it has used blood biomarkers such as GFAP and UCH-L1, and non-contrast CT CDEs as input variables.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, there are studies describing models to predict the functional outcome or The Glasgow Outcome Scale-Extended, 5,[25][26][27][28][29] and more recent studies using images as inputs. 8,30,31 Furthermore, there are studies in the literature similar to ours that describe models for predicting in-hospital mortality, 29,[32][33][34][35] early mortality, [36][37][38] discharge position, 39,40 need for hospital admission, 6 emergency neurosurgery, 41 and length of hospital stay. 4 In addition to contributing to the body of knowledge by describing the efficacy of incorporating ML into patient care to predict multiple outcomes simultaneously in TBI patients, this study is unique since it has used blood biomarkers such as GFAP and UCH-L1, and non-contrast CT CDEs as input variables.…”
Section: Discussionmentioning
confidence: 77%
“…Цель: оценить информативность параметров радиомики по данным диффузионно-куртозисной магнитно-резонансной томографии для выявления микроструктурных повреждений головного мозга у пациентов при диффузном аксональном повреждении и прогнозирования его исходов. Работ с использованием радиомики при черепно-мозговой травме крайне мало [8][9][10][13][14][15][16], и в основном они…”
Section: оригинальные статьи оRiginal Researchunclassified
“…At the same time, by complementing with other information such as clinical or laboratory data, radiomics improves diagnostic e ciency to an acceptable level for clinical practice. Radiomics has been widely applied in clinical research of the central nervous system, such as predicting hematoma expansion in hypertensive intracerebral hemorrhage, 9,10 predicting hematoma expansion in traumatic brain injury, 11,12 etiological classi cation of intracranial aneurysm rupture, 13 and etiological classi cation of intracranial hemorrhage. 14 Although radiomics has been widely used in central nervous system research, there have been no reported studies on predicting the duration of invasive mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%